Parent-child relationship in contemporary Singapore - Tamil Vani Gunasilan (2010)
This analysis suggests that there are social class differences in parenting style and different parenting style could impact on their parent-child relationships in Singapore. Social class differences in occupations are the major factors contributing to the adoption of different parenting style. Local middle-class parents adopt permissive parenting that is similar to their Western counterparts in similar social class while local working-class parents adopt authoritarian parenting. Existing family studies state that wide-spread Westernized influence into Asian societies has affected parent-child relationships. This research indicates that it is less about Western versus Asian parenting, but more about social class differences that, in turn, impacts parent-child relationships.